Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T20:02:26+01:00
A) -[-(-8x + 2)-4xy -(10 - 2x) + 6x = (-8x + 2) - 4xy - 10 + 2x + 6x =
= -8x + 2 - 4xy - 10 + 2x + 6x = - 4xy - 8
b) 2ab² - (4ab² - 3b² - a) - [- (- 12ba² + 3a²b²)] + 16a²b =
= 2ab² - 4ab² + 3b² + a - [12ba² - 3a²b²] + 16a²b =
= 2ab² - 4ab² + 3b² + a - 12ba² + 3a²b² + 16a²b =
= - 2ab² + 4a²b + 3b² + a + 3a²b² = 3a²b² - 2ab² + 4a²b + 3b² + a
c) - 1,2xy - 8y² - (- 5yx + 10,5y² - 8,3) - (- 2,3 + 3,8xy =
= 1,2xy - 8y² + 5xy - 10,5y² + 8,3 + 2,3 - 3,8xy = 2,45xy - 18,5y² + 10,6
d) 8a²bc - (4abc² + 10ab²c) - [ - (4abc² + 10ab²c) - 8a²bc] =
= 8a²bc - 4abc² - 10ab²c - [- 4abc² - 10ab²c - 8a²bc] =
= 8a²bc - 4abc² - 10ab²c + 4abc² + 10ab²c + 8a²bc = 16a²bc
e) (3,5x² - 7,5y) - 5 - (1,5y + 5,5x² - 3,2) + 2x² + 9y =
= 3,5x² - 7,5y - 5 - 1,5y - 5,5x² + 3,2 + 2x² + 9y = - 6 + 3,2 = - 2,8
f) - 3,2x + ( - 0,8y + 2z) - (1,2y - 0,8x) - (2z - 2,4x) =
= - 3,2x - 0,8y + 2z - 1,2y + 0,8x - 2z + 2,4x = - 2y
figury
a)
2(x+y + 2x + y) = 2(3x + 2y) = 6x + 4y = 6 razy 4 + 4 razy 5 = 24 + 20 = 44
b)
x + y - 5 + 3x + 4 + x + y + 6 = 5x + 2y + 1 = 5 razy 4 + 2 razy 5 + 1 = 20 + 10 + 1 = 31
c)
3x + 2y + 3x + 2 + 2x + y = 8x + 3y + 2 = 8 razy 4 + 3 razy 5 + 2 = 32 + 15 + 2 =
= 49
1 5 1